Физико-химические условия образования ртутистого золота на Аu-Hg месторождениях (термодинамическое моделирование) - Гущина, Л.; Наумов, Е. (Розробка родовищ, 2017)
Purpose. To carry out computer thermodynamic modeling of gold and mercury behaviour in the context of their common occurrence and formation of mercuric gold in hydrothermal solutions C¯ – HCO₃¯ – Na⁺ and Cl¯ – Na⁺ – Ca²⁺ with the use of “Chiller” programme. Findings. Relying upon the previously obtained data of fluid inclusion studies and thermodynamic modeling, basic geological and geochemical conditions of occurrence have been identified; physical and chemical factors defining gold deposits with different mercury content have been determined.